Comparison of the radioisotope dilution-coated charcoal method and a microbiological method (L. leichmannii) for measuring vitamin B(12) in serum - Raven, J. L. (1966)
A comparison has been made of the radioisotope dilution-coated charcoal method and a microbiological assay (with L. leichmannii as test organism) for determining the concentration of vitamin B(12) in serum. A satisfactory correlation was found between the results of the two methods. Under appropriate conditions the reproducibility of the radioisotope method compared favourably with that of the microbiological method.